Optimasi Jaringan Irigasi Perpipaan Berdasarkan Karakteristik Hidraulis dan Biaya di Pertanian Lahan Kering - Iman Muhardiono; Budi Kartiwa; Adang Hamdani; Nani Heryani (Balai Teknik Irigasi, 2020)
In dry lands, limited annual rainfall rate as well as its uneven temporal and spatial distribution causes a heavy constraint on agricultural activities. Utilization of proper irrigation method can overcome these limitations so that water demand can be fulfilled in an efficient and effective manner. Currently, pipe irrigation has been widely used to improve irrigation efficiency and crop productivity. However, in practice, the designs which had been made usually not yet optimum and efficient so that the expected discharge output can be excessive or less than expected. Therefore, design optimization is required by considering hydraulic characteristics and costs. The research was conducted to obtain optimal pipe irrigation network design through scenario analysis of pipe dimensions based on hydraulic modeling in the EPANET 2.0 application. The research was conducted in South Lampung Regency with a research block area of 1 ha. The analysis was conducted in 15 scenarios of irrigation networks with different combination of pipe diameter. The results showed that the simulated pipe diameter combination scenario can give varying results for the cost component and the hydraulic conditions of water in the pipe. The best combination is Scenario 7 with a combination of main pipe with a diameter of 48 mm and a sub-main pipe with a diameter of 22 mm which can optimally fulfill the plant water requirement at a relatively economical cost.